Chemical composition and antimicrobial activity of the essential oil from aerial parts of Micromeria debilis Pomel from Algeria. Issue 5 (2nd September 2016) - Gherib, Mohammed; Bekhechi, Chahrazed; Paoli, Mathieu; Atik Bekkara, Fewzia; Bighelli, Ange; Casanova, Joseph; Tomi, Félix
Abstract: For the first time, the chemical composition of the essential oil of aerial parts of Micromeria debilis was determined. The essential oil was obtained by hydrodistillation and analyzed by GC(FID), GC/MS and 13 C-NMR. In total, forty-two constituents were identified representing 92.4% of the total oil, β-Pinene (19.3%) being the major monoterpene beside geranial (8.7%) and linalool (6.5%). Germacrene D (11.4%) and (E) -β-caryophyllene (8.0%) were the main sesquiterpene hydrocarbons while oxygenated sesquiterpenes were mainly represented by caryophyllene oxide (8.0%). Eight samples of essential oil of M. debilis collected in two locations exhibited similar chemical composition evidencing a chemical homogeneity. The essential oil showed moderate antimicrobial activity, with MIC values between 2 μL/mL and 6 μL/mL. The lowest MIC values (2.0 μL/mL) were measured for K. pneumoniae, S. typhimurium and C. albicans .